Assessing Islamic Bank Financial Distress Across Five ASEAN Economies - Ervita Safitri; Abid Djazuli; Mister Candera (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study diagnoses and compares financial distress levels in Islamic banks across five Association of Southeast Asian Nations (ASEAN) countries, explicitly linking divergent resilience to the national institutional contexts. It identifies the key determinants of distress, addressing a gap in multi-model, cross-country sectoral assessments. Methodology: A longitudinal, multi-model framework was used to analyze secondary panel data (2015–2025) from leading Islamic banks in Indonesia, Malaysia, Thailand, the Philippines, and Brunei. Financial distress was assessed using five models (Altman Z, Springate S, Zmijewski X, Grover G, and Taffler Z), followed by a comparative trend analysis. Results: The results show a clear contrast: Maybank Islamic is resilient, while Al-Amanah Islamic is distressed. Profitability is the main distress indicator, but the strongest explanation is institutional context, where Malaysia’s stronger regulation, Shariah governance, and deeper Islamic capital markets enhance bank resilience. Conclusions: The financial resilience of ASEAN Islamic banks is determined more by the national institutional ecosystem than by bank-specific factors. Multi-model analysis provides nuanced diagnostics, emphasizing profitability and the balance sheet structure. Limitations: The generalizability of the findings may be constrained by the focus on five banks and models. Contributions: Theoretically, this study pioneers a comparative, multi-model distress analysis of Islamic banks, interpreting model divergence through an institutional lens. Practically, it offers evidence-based guidance for regulators to enhance stability through improved Shariah governance and multi-model early warning systems.